2014
DOI: 10.1371/journal.pone.0094144
|View full text |Cite
|
Sign up to set email alerts
|

Heteroconium chaetospira Induces Resistance to Clubroot via Upregulation of Host Genes Involved in Jasmonic Acid, Ethylene, and Auxin Biosynthesis

Abstract: An endophytic fungus, Heteroconium chaetospira isolate BC2HB1 (Hc), suppressed clubroot (Plasmodiophora brassicae -Pb) on canola in growth-cabinet trials. Confocal microscopy demonstrated that Hc penetrated canola roots and colonized cortical tissues. Based on qPCR analysis, the amount of Hc DNA found in canola roots at 14 days after treatment was negatively correlated (r = 0.92, P<0.001) with the severity of clubroot at 5 weeks after treatment at a low (2×105 spores pot−1) but not high (2×105 spores pot−1) do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 67 publications
1
32
1
Order By: Relevance
“…Heteroconium chaetospira (Grove) M. B. Ellis has been reported to suppress clubroot disease in Chinese cabbage plants (Narisawa et al, 2005). Lahlali et al (2014) reported that Heteroconium chaetospira (syn. C. chaetospira) suppressed clubroot (Plasmodiophora brassicae) disease via the upregulation of host genes involved in jasmonic acid, ethylene, and auxin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Heteroconium chaetospira (Grove) M. B. Ellis has been reported to suppress clubroot disease in Chinese cabbage plants (Narisawa et al, 2005). Lahlali et al (2014) reported that Heteroconium chaetospira (syn. C. chaetospira) suppressed clubroot (Plasmodiophora brassicae) disease via the upregulation of host genes involved in jasmonic acid, ethylene, and auxin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…SA treatment alone does not seem to be sufficient. One solution could be by biocontrol organisms, which could induce the plant's immune system, as shown for the interaction of Brassica napus with P. brassicae, where JA/ethylene pathways could be induced (Lahlali et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…PR genes and JAdependent genes were not differentially regulated (Su et al 2013). A similar study on a dark-septate endophyte on oilseed rape was carried out by Lahlali et al (2014), in which PR-2 (β-1,3-glucanase) and PAL was up-regulated when the plants were inoculated with the endophyte before inoculation with Plasmodiophora brassicae.…”
Section: Examples Of Fungal Endophytes Inducing Resistancementioning
confidence: 80%
“…Since the control effect is only local, it would require a systemic colonisation of the host plant part where the pathogen might attack. Correspondingly, colonisation of oilseed rape roots with the dark-septate endophyte Heteroconium chaetospira, measured by qPCR, was negatively correlated to clubroot symptoms (Lahlali et al 2014). However, increased pathogen inoculum reduced the control effect, indicating the limitation of competition as a mechanism under high disease pressure.…”
Section: Competitionmentioning
confidence: 95%
See 1 more Smart Citation